Halocnemum strobilaceum (Pall.) M.Bieb.: a review of its botany, phytochemistry, pharmacology and ethnobotany - Fatemeh Nasernakhaei; Mahyar Zahraei (Institue of Medicinal Plants, ACECR, 2021)
Background: Halocnemum strobilaceum (Pall.) M.Bieb. (Amaranthaceae) is a halophyte commonly used in traditional medicine to treat fever, jaundice, hair loss, dysmenorrhea, and headache. Other uses of H. strobilaceum include using its aerial parts extract as probiotics in aquaculture feed and a preservative in the food and beverage industries. Objective: This review will summarize the current state of knowledge available on this plant's botany, phytochemistry, pharmacology, and ethnobotany. Methods: The databases of Google Scholar, Web of Science, PubMed, Scopus, and SID were searched systematically, with no date limitation for articles published in English. Results: H. strobilaceum extracts are a rich source of anthocyanins, saponins, caffeic acid, flavonoids, coumarins, phenolic compounds, alkaloids, and fatty acids. The bioactivities ascribed to H. strobilaceum extracts are anticancer, antimicrobial, and antioxidant activities. They also can be used as insecticides against pests of stored products. Conclusion: Considering the different activities and many properties of H. strobilaceum it seems to be a suitable option for further experimental and clinical trial research.